Analisis Perbandingan Penentuan Harga Pokok Produksi Dengan Metode Full Costing Dan Variabel Costing Pada Usaha Kain Tenun Di Lembang Kolesawangan Kecamatan Malimbong Balepe Kabupaten Tana Toraja - Srimelin Dahyuni; Jemi Pabisangan Tahirs; Mince Batara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Based on the aim of this research is to find out the comparison of full costing methods and variable costing in determining the cost of production for woven fabric business in Lembang Kolesawangan, Malimbong Balepe district, Tana Toraja Regency. This type of research uses quantitative descriptive data obtained through interviews, observation and documentation. Furthermore,analyzing the data by comparing the full costing method dan variable costing. The results show the by calculating using the full method and variabel costing, where full costing obtains a higher value, namely Rp.2.671.000 because the full costing method takes into accound all the elements of cosct, both fixed and variable. Compared to variabel costing, you only get a value of Rp,2.191.925 because variabel costing is only variable costs that are included in inventory and cost of good sold.